2019
DOI: 10.1186/s12934-019-1071-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteome analysis in an Escherichia coli CyDisCo strain identifies stress responses related to protein production, oxidative stress and accumulation of misfolded protein

Abstract: BackgroundThe Twin-arginine translocation (Tat) pathway of Escherichia coli has great potential for the export of biopharmaceuticals to the periplasm due to its ability to transport folded proteins, and its proofreading mechanism that allows correctly folded proteins to translocate. Coupling the Tat-dependent protein secretion with the formation of disulfide bonds in the cytoplasm of E. coli CyDisCo provides a powerful platform for the production of industrially challenging proteins. In this study, we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…Consistently, others (Bradley et al, 2016, Crabb, Moore et al, 2010, Theil, Tosha et al, 2016) have suggested that the chemical content and structure of iron inside the core is polyphasic or heterogenous and may not be packed regularly. Moreover, the enhanced deposition of Fe-biomineral inside the cavity is presumably due to protein overexpression in the recombinant bacteria, and that this stressful environment facilitates the active conversion of Fe 2+ to Fe 3+ (Guerrero Montero, Dolata et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, others (Bradley et al, 2016, Crabb, Moore et al, 2010, Theil, Tosha et al, 2016) have suggested that the chemical content and structure of iron inside the core is polyphasic or heterogenous and may not be packed regularly. Moreover, the enhanced deposition of Fe-biomineral inside the cavity is presumably due to protein overexpression in the recombinant bacteria, and that this stressful environment facilitates the active conversion of Fe 2+ to Fe 3+ (Guerrero Montero, Dolata et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…pKRK38 was made by polymerase chain reaction (PCR) amplification using pKRK7 as a template and primers Mature_hGH_F (5′‐ATGTTCCCAACCATTCCCTTATCCA‐3′) and Mature_hGH_R (5′‐CATACATGTTCCTCTGTGGTAGGGT‐3′) as forward and reverse primers. PCR solutions, enzymes and reaction conditions were as described in Guerrero‐Montero et al ().…”
Section: Methodsmentioning
confidence: 99%
“…Protein samples were resolved by reducing sodium dodecyl sulfate‐polyacrylamide gel electrophoresis (SDS‐PAGE) and analyzed using Coomassie blue staining and western blotting. All immunoblotting procedures were as described in Guerrero‐Montero et al (). Periplasmic hGH activity was assayed using an hGH bioassay (PathHunter® Human Growth Hormone Bioassay Kit, Sigma) using the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Protein digestion, liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis, protein identification and quantification methodology used to analyze the proteome of cells producing periplasmic hGH using different signal peptides and control cells with an empty expression vector have been described in detail previously (Guerrero Montero et al, 2019). In short, proteins in whole cell lysates were separated by SDS-PAGE and subsequently each lane was cut into 10 equidistant pieces prior to in-gel digestion using trypsin.…”
Section: Proteome Analysis Of Hgh Producing Cellsmentioning
confidence: 99%
“…The generated peptides were eluted from the gel to an aqueous solution by ultrasonication and the concentrated peptide mixture was subjected to LC-MS/MS analysis performed on an EASY-nLC II coupled to an LTQ Orbitrap (Thermo Fisher Scientific) mass spectrometer. Peptides were separated on in-house self-packed columns (Guerrero Montero et al, 2019) FIGURE 1 | Periplasmic hGH production screening and proteome analysis of hGH producing cells. (A) On the left: Periplasmic production screening of hGH fused to different signal peptides (DsbA sp , Hbp sp , OmpA sp , and PhoA sp ) was done in standard 24-well plates (i).…”
Section: Proteome Analysis Of Hgh Producing Cellsmentioning
confidence: 99%